Protein-energy malnutrition and worse outcomes after major cancer surgery: A nationwide analysis - Jin, Jiewen; Zhu, Xianying; Deng, Zhantao; Zhang, Pengyuan; Xiao, Ying; Han, Hedong; Li, Yanbing; Li, Hai (Frontiers in Oncology, 2023)
Background: Protein-energy malnutrition (PEM) has been recognized as a poor prognostic factor in many clinical issues. However, nationwide population studies concerning the impact of PEM on outcomes after major cancer surgery (MCS) are lacking. We aimed to evaluate the postoperative outcomes associated with PEM following MCS. Methods: By using the Nationwide Inpatient Sample database, data of patients undergoing MCS including colectomy, cystectomy, esophagectomy, gastrectomy, hysterectomy, lung resection, pancreatectomy, or prostatectomy were analyzed retrospectively from 2009 to 2015, resulting in a weighted estimate of 1,335,681 patients. The prevalence trend of PEM, as well as mortality and major complications after MCS were calculated. Multivariable regression analysis was applied to estimate the impact of PEM on postoperative outcomes after MCS. Results: PEM showed an estimated annual percentage increase of 7.17% (95% confidence interval (CI): 4-10.44%) from 2009 to 2015, which contrasts with a 4.52% (95% CI: -6.58--2.41%) and 1.21% (95% CI: -1.85--0.56%) annual decrease in mortality and major complications in patients with PEM after MCS. PEM was associated with increased risk of mortality (odds ratio (OR)=2.26; 95% CI: 2.08-2.44; P < 0.0001), major complications (OR=2.46; 95% CI: 2.36-2.56; P < 0.0001), higher total cost ($35814 [$22292, $59579] vs. $16825 [$11393, $24164], P < 0.0001), and longer length of stay (14 [9-21] days vs. 4 [2-7] days, P < 0.0001), especially in patients underwent prostatectomy, hysterectomy and lung resection. Conclusions: PEM was associated with increased worse outcomes after major cancer surgery. Early identification and timely medical treatment of PEM for patients with cancer are crucial for improving postoperative outcomes.